Bringing engineering into primary science classrooms using engineering design and community of practice approach—An evaluation of STEM × Play program - Lai, Mun Yee; Cheng, Eva (Frontiers in Education, 2023)
Due to the rapid growth of STEM-skilled jobs, there is an urge of introducing engineering in earlier years of schooling to not only flourish students' motivation and interest but to also acquire the required skills for surviving in the high digital demand environment. This paper aims to share an innovative pedagogy -STEM x Play in-curriculum program and to report the post-program evaluation of primary school students' perceptions about and attitudes towards learning STEM and teachers' perception of teaching STEM. There was evidence of positive student learning outcomes including critical skills needed for STEM professions such as comfort with failure, collaboration, critical thinking and problem solving. Mentors from universities and industries were found crucial for improving teachers' STEM skills.